Properties of Synthetic Two-Dimensional Materials and Heterostructures - Lin, Yu-Chuan (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis represents a significant advance in our understanding of the synthesis and propertiesof two-dimensional (2D) materials. The author's work breaks new ground in the understanding of a number of 2D crystals, including atomically thin transition metal dichalcogenides, graphene, and their heterostructures, that are technologically important to next-generation electronics. In addition to critical new results on the direct growth of 2D heterostructures, it also details growth mechanisms, surface science, and device applications of "epi-grade" 2D semiconductors, which are essential to low-power electronics, as well as for extending Moore's law. Most importantly, it provides an effective alternative to mechanically exfoliate 2D layers for practical applications. .